Characteristics of patients with newly diagnosed hematological malignancies referred for echocardiography - Kępski, Jarosław; Szmit, Sebastian; Lech-Marańda, Ewa (Frontiers in Oncology, 2024)
Objective The importance of cardio-hemato-oncology programs is increasing. The main aim of the study was to identify all coexisting cardiovascular disorders in patients with new hematological malignancies referred for echocardiography during baseline evaluation before anticancer therapy. Material and Methods The study was based on 900 echocardiographic examinations performed within 12 months at the Institute of Hematology and Transfusion Medicine in Poland: 669 tests (74.3%) were dedicated to hemato-oncology patients at the different stages of cancer therapy, however almost every a third of the tests (277, 30.8%) were the part of a baseline evaluation before starting of first line of anticancer therapy due to newly diagnosed hematological malignancies. Results The group of 277 patients with new hematological malignancies (138 women, 49.82%) with a median age of 66 years (interquartile range: 53-72 years) was included in the main analyses. The three most frequent new histopathological diagnoses were: non-Hodgkin lymphoma (63 cases; 22.74%), acute myeloid leukaemia (47 cases; 16.97%), and multiple myeloma (45 cases; 16.25%). The three most common clinical cardiology disorders were: arterial hypertension (in 133 patients, 48.01%), arrhythmias (48 patients, 17.33%), and heart failure (39 patients, 14.08%). Among 48 patients with arrhythmias there were 22 cases with atrial fibrillation. The most frequently detected echocardiographic abnormality was Left Atrial Volume Index >34 ml/m2 which was present in 108 of 277 patients (38.99%) and associated with a significantly greater chance of concomitant diagnosis of arrhythmias (OR=1.98; p=0.048) especially atrial fibrillation (OR=3.39; p=0.025). The second most common echocardiographic finding was diastolic dysfunction 2nd or 3rd degree revealed in 43 patients (15.52%) and associated with a greater chance of simultaneous diagnosis of heart failure (OR=8.32; p<0.0001) or arrhythmias (OR=4.44; p<0.0001) including atrial fibrillation (OR=5.40; p=0.0003). Conclusions In patients with newly diagnosed hematological malignancies left ventricular diastolic dysfunction is a common abnormality in echocardiography and may determine diagnoseis of heart failure or arrhythmias.